Examination of Consumers’ Perceived Quality and Willingness to Buy in the Context of Price Variability and Frequency of Price Change: A Study of Retail Products - ATILGAN, Kalender Özcan; KANGAL, Evrim Ersin; TALASLIOĞLU, Muharrem (Gadjah Mada International Journal of Business, 2024)
Marketing managers are able to influence consumers' perceptions of quality and their willingness to buy, using the frequency of price changes and price variability. This study aims to examine the differences in the frequency of price changes and price varia- bility, in terms of the perceived quality and the willingness to buy. For this purpose, using values calculated according to the average and standard deviation of the market price of a specified product, we obtained two different price variations, ±1σ and ±2σ, and price stim- uli determined at two different frequencies of price changes (three and seven times were considered), which resulted in four different participant groups. At the end of the study, a statistically significant difference was only found between consumers in the low price var- iability and infrequent price change condition and consumers in the high price variability and infrequent price change condition, in terms of the perceived quality.